Trends in UK meat consumption: analysis of data from years 1–11 (2008–09 to 2018–19) of the National Diet and Nutrition Survey rolling programme - Stewart, C; Piernas, C; Cook, B; Jebb, SA (Elsevier, 2021)
Background High meat consumption, particularly red meat and processed meat, negatively affects our health, while meat production is one of the largest contributors to global warming and environmental degradation. The aim of our study was to explore trends in meat consumption within the UK and the associated changes in environmental impact. We also aimed to identify any differences in intake associated with gender, ethnicity, socioeconomic status, and year of birth.